ANALISIS BUKU AJAR (LEHRWERKANALYSE) BAHASA JERMAN STUDIO D DAN NETZWERK DALAM PENGAJARAN BAHASA JERMAN DI STBA YAPARI-ABA BANDUNG - Tintin Agustina; Dasim Karsam (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2018)
A textbook plays a very crucial role in foreign language teaching. On the one hand, it deals with linguistic and cultural phenomena; Moreover, it controls the whole learning process for a certain period of time. This research focuses on the main learning materials and media used by lecturers and students of German Department at STBA YAPARI. The purpose of the study is to find a suitable textbook for them. In order to reach the goal of the investigation, this study uses the theoretical foundations of Rösler & Würffel (2014: 17-32) on the analysis of learning materials and media in a form of the textbook analysis method, namely the analysis of